Understanding motivations to participate in an observational research study: Why do patients enroll?. (15th March 2016) - Soule, Michael C.; Beale, Eleanor E.; Suarez, Laura; Beach, Scott R.; Mastromauro, Carol A.; Celano, Christopher M.; Moore, Shannon V.; Huffman, Jeff C.
ABSTRACT: By understanding common motivations for participating in observational research studies, clinicians may better understand the perceived benefits of research participation from their clients' perspective. We enrolled 164 cardiac patients in a study about the effects of gratitude and optimism. Two weeks post-enrollment, participants completed a four-item questionnaire regarding motivations for study enrollment. Altruistic motivation ranked highest, while intellectual, health-related, and financial motivations rated lower. Four subgroups of participants emerged, each with distinct characteristics and different priorities for participating. These findings may help front-line clinicians to understand which motivations for participation apply to their clients who enroll in non-treatment-based research projects.